All the World's Futures : La Biennale di Venezia, 56. Esposizione internazionale d'arte /. - Biennale di Venezia / International Art Exhibition Venice 2015; Gyalui, Luz; Enwezor, Okwui (Venice : Marsilio Editori, 2015)
Rather than one overarching theme, the 56th International Art Exhibition of the Biennale is informed by a layer of intersecting filters. These filters are a constellation of parameters that circumscribe multiple ideas which will be touched upon to imagine and realize a diversity of practices. All the World's Futures employs as a filter the historical trajectory that the Biennale itself, over the course of its one hundred and twenty years existence has run over. A filter through which to reflect on both the current 'state of things' and the 'appearance of things.' At its core is the notion of the exhibition as a stage, where historical and counter-historical projects are explored. Within this framework the main aspects of the 56th Biennale Exhibition solicit and privilege new proposals and works conceived specifically by invited artists, filmmakers, choreographers, performers, composers, and writers.
Abdul, Lida ; Abdullah Bulhiah, Mohammed ; Abidi, Bani ; Abidin, Adel ; Kleyebe Abonnec, Mathieu ; Aghaei, Amin ; Aghelli, Ghodratollah ; Ahmadi, Shahriar ; Ahovan, Parastoo ; Ahrarnia, Farhad ; Aivazian, Haig ; Alakbarov, Rashad ; Al Ani, Latif ; et al.
Catalog of the 56th Biennale di Venezia, held May 9-November 22, 2015, Venice, Italy.
kunstcatalogus